Preparation and Characterization of high surface area material from natural Syrian zeolite TS-7 - الركاد, حسام (Latakia University Journal -Basic Sciences Series, 2023)
The porous silica Si- TS-7 has been prepared from Syrian natural zeolite TS-7. Natural zeolite was treated with hydrochloric acid 10%wt for 24h at 20oC. The product was filtered to remove the precipitate. Filtrate has been used to produce solid base in previous work. The precipitate has washed with distilled water and dried at 110oC for 24h and calcined at 500oC for 4h. The resulted material Si-TS-7 was characterized by TG-DTA and FTTR, XRD BET methods. The results showed that the Si-TS-7 consist of silica mainly. Textural properties study showed that the adsorption isotherm belongs to type IV according to the classification of Singh and colleagues, which is characterized by the presence of a hysteresis loop that indicates the presence of the phenomenon of capillary condensation and presence of high specific surface area of 412m2/g compared to crude zeolite.